The Description of Knowledge of Type 2 Diabetes Mellitus Patient Measured by Simplified Diabetes Knowledge Scale Indonesia Version (SDKS-INA) - Perdani Adnin Maiisyah; Zullies Ikawati; Zainol Akbar Zainal (Majalah Farmaseutik, 2022)
Knowledge of diabetes is the important determinant to practice the self-care thus, the therapy goals of diabetes achieved. The aim of the study is to assess the knowledge of type 2 DM patients using SDKS-INA. This research is an observational study, with data collected in the community of the Yogyakarta province from January - May 2020. The assessment of knowledge of type 2 DM patients was measured by Simplified Diabetes Knowledge Scale in Bahasa Indonesia 1 for the non-insulin user (SDKS-INA1) and SDKS-INA2 for insulin user. Ninety-six of the non-insulin user and 28 insulin user type 2 DM participated in this study. The percentage of non-insulin user type 2 DM patients with a high level of knowledge was 53.13%, while in those in insulin user was 60,70%. However, high knowledge level is not the intention to discontinue giving education. The knowledge level also should be assessed routinely as well as delivering sustainable diabetes education.